2004
DOI: 10.3748/wjg.v10.i9.1250
|View full text |Cite
|
Sign up to set email alerts
|

Significance of vascular endothelial growth factor expression and its correlation with inducible nitric oxide synthase in gastric cancer

Abstract: AIM:To investigate the clinical significance of the expression of VEGF 165 mRNA and the correlation with vascular endothelial growth factor (VEGF) protein and inducible nitric oxide synthase (iNO) in human gastric cancer. METHODS:We tested VEGF 165 mRNA expression in 31 cases of resected gastric cancer specimens and normal paired gastric mucosae by RT-PCR. Total RNA was extracted with TRIzol reagents, transcribed into cDNA with oligo (dT 15 ) priming, inner controlled with β-actin expression and agarose gel is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(20 reference statements)
1
3
0
2
Order By: Relevance
“…In this study, VEGF expression tended to associate with iNOS immunoreactivity. These findings are in line with reports of Song et al In gastric cancer, they reported a correlation between VEGF and iNOS, and VEGF expression was related to TNM stages [44].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, VEGF expression tended to associate with iNOS immunoreactivity. These findings are in line with reports of Song et al In gastric cancer, they reported a correlation between VEGF and iNOS, and VEGF expression was related to TNM stages [44].…”
Section: Discussionsupporting
confidence: 87%
“…Zhang et al showed that in over 50% of gastric cancer patients, increased NOS2 expression was associated with elevated rates of lymph node metastasis, vascular invasion, distant metastasis, and tumor node metastasis stage (197). Moreover, NOS2 is also associated with increased density of intratumor microvessels and angiogenesis in gastric cancer (67,161). In addition, NOS2 has been shown to be positively correlated to lymphangiogenesis and lymphatic metastasis in gastric cancer (82).…”
Section: Gastric Cancermentioning
confidence: 99%
“…VEGF and h-actin expression in serial sections were determined by immunostaining using monoclonal antibodies against VEGF and h-actin (1:100, Santa Cruz Biotechnology). VEGF staining was scored semiquantitatively as Song's method with minor modification (24). Briefly, the shade of staining was assigned to 0 to 3 scores according to staining density, and the percentage of staining cell was also assigned to 0 to 3 scores according to the percentage of positive staining cells.…”
Section: Cell Culturementioning
confidence: 99%